Penerapan Pembelajaran PBL Terhadap Dimensi Bernalar Kritis dan Gotong Royong pada Pembelajaran IPAS - Safira, Anggita Eka; Kartinah, Kartinah (Universitas PGRI Semarang, 2025)
In this study, the researcher is interested in researching the influence of PBL learning on the profile of Pancasila students in the dimension of critical reasoning and mutual cooperation. The purpose of this study is to determine the influence between PBL learning and the lecture method (conventional) which is associated with the dimension of the profile of Pancasila students with critical reasoning and mutual cooperation. This study uses a mix method approach with a quasi-experimental research design and direct interview techniques. Data colection techniques use questions, documentation, and interview questionnaires. The research population is students of grade V SD N Karanganyar Gunung 02 Semarang. The research sample used class 5C as the control class, and 5B as the experimental class. Based on the results of the research, the results of the posttest were obtained in the experimental class 84 and in the control class 77. Then a hypothesis test using the N-Gain test obtained a result of 53.60 or 54%, including in the category of quite effective. Referring to these results, it can be concluded that the influence of PBL learning on the dimension of critical reasoning and mutual cooperation is quite effective applied to grade V students of SD N Karanganyar Gunung 02 Semarang.